ECONOMY AND LAW IN A PLURAL WORLD - Heribert, Koeck Franz (Anales Universitatis Apulensis Series Jurisprudentia, 2012)
The basic idea of free market economy as developed by Smith and Ricardo is attractive. Competition among those engaging in economic activities will induce them to offer always better products for an always cheaper price. Not only the consumers will profit from this but also those producers who are most successful in keeping up with this development, because their profit will rise. In contrast, those producers who are not successful in offering sufficiently good products at a sufficiently favourable price will make no profit but loss. Keywords: free market economy, economic activities, Competition, producers, good products.